2010
DOI: 10.1016/j.breast.2010.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous versus oral vinorelbine plus capecitabine as second-line treatment in advanced breast cancer patients. A retrospective comparison of two consecutive phase II studies

Abstract: Vinorelbine (i.v.) plus capecitabine (oral) combination therapy is active in anthracycline/taxane pretreated patients with metastatic breast cancer. Availability of oral vinorelbine provides this combination in an all-oral formulation. Two consecutive phase II trials differing only in vinorelbine administration routes evaluated their respective activities and tolerabilities in this population. In the i.v. group (n = 38) disease control was 61% (37% PR, 24% SD), median TTP 6.8 months and median survival 11.3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Subsequent trials showed that there was a substantial equivalence between the iv and the oral formulations of VRB, even if this latter was characterized by a higher rate of haematological toxicity [35]. In all these studies, VRB and CAPE were administered on days 1 and 8, according to the approved standard schedule.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent trials showed that there was a substantial equivalence between the iv and the oral formulations of VRB, even if this latter was characterized by a higher rate of haematological toxicity [35]. In all these studies, VRB and CAPE were administered on days 1 and 8, according to the approved standard schedule.…”
Section: Introductionmentioning
confidence: 99%
“…In other phase II trials in which the combination of capecitabine and vinorelbine was administered to patients with breast cancer pretreated with anthracyclines and taxanes Table (4) [25][26][27][28][29][30][31] , the RRs obtained ranged between 33% and 70%. In these studies, the median time to progression (TTP) ranged from 4.5 months to 10 months and the median OS was within 10 months and 30.4 months.…”
Section: Discussionmentioning
confidence: 99%
“…The only grade 3/4 toxicities were neutropenia (19%) and hand-foot syndrome (9%). The retrospective comparison of two consecutive phase II studies conducted by Lorusso et al [14] demonstrated a similar toxicity profile and response rate for this combination. Interestingly, no hand-foot syndromes were observed in our study despite the use of similar doses of UFT.…”
Section: Discussionmentioning
confidence: 99%
“…Dose levels were determined based on the results of the previous single-agent and combination chemotherapy trials [11,12,13,14,16,17]. The escalated dose design was based on the Fibonacci ‘3 + 3’ schedule [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation